Mechanoreceptor cells on the tertiary pulvinus of Mimosa pudica L. - Visnovitz, Tamás; Világi, Ildikó; Kristóf, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2005)
Sensitive plant (Mimosa pudica L.) is famous for its rapid leaf movements, so there are several of scientific essays about this plant in the international literature. Nowadays the mechanism of leaf dropping is well-known, but there are a lot of questions which are unanswered. One of these unanswered questions is how this plant can feel mechanical stimuli. The mechanoreceptor cells have not been identified (Shimmen 2001). In this article some mechanoreceptive cells are described on tertiary pulvini of mimosa. As electrophysiological studies show, these excitable cells produce receptor potentials which can control the leaf movements through the action of motor cells. During the electronmicroscopic observation, plasmodesmata were found between that receptor cells and excitable ‘motos cells’, which contain double vacuole system, so action potential can pass down from receptors to pulvinar motor cells, which means that these cells can be functional mechanoreceptors on tertiary pulvini.